METODE PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MADRASAH TSANAWIYAH NURHIDAYAH HANTAKAN KABUPATEN HULU SUNGAI TENGAH - Hatmiah Hatmiah (CV. ADIBA AISHA AMIRA, 2023)
This research is about the learning method of Islamic cultural history at Madrasah Tsanawiyah Nurhidayah Hantakan, Hulu Sungai Tengah Regency. The purpose of this study was to use the Islamic cultural history learning method at Madrasah Tsnawiyah Nurhidayah Hantakan, Hulu Sungai Tengah Regency. The subjects in this study were a teacher of Islamic cultural history and several students at Madrasah Tsanawiyah Nurhidayah Hantakan, Hulu Sungai Tengah Regency. This research is a field research and to obtain data it is done by means of observation, interviews and documentaries. The data processing technique uses data reduction, data display, data verification. Processed data were analyzed using qualitative discrete analysis. This research produced findings which explained that the learning methods of Islamic cultural history at Madrasah Tsanawiyah Nurhidayah Hantakan, Hulu Sungai Tengah Regency, were the lecture method, the story method and the question and answer method.